PENERAPAN METODE CUSTOMER RELATIONSHIP MANAGEMENT PADA ECOMMERCE BERBASIS ANDROID (STUDI KASUS : PT KIMIA FARMA) - M.reza redo; Ridwan Yusuf (Jurnal Multimedia dan Android (JMA), 2020)
Abstract The data processing process related to sales data and the availability of goods that are currently running still uses conventional recording, namely the absence of a system that can process data automatically to speed up the processing of Customer Relationship Management (CRM) is a method used to facilitate the communication process between consumers and companies for the purpose of creating a sense of comfort in consumers against the company. One proof of the need for a system desired by the owner of PT.KIMIA FARMA is to want to have a system that can help promote and introduce his own business and also increase sales without even having to require a large cost in conducting the advertising process. research title